Impact of adhesive application errors on dentin bond strength of resin composite - Benjamin Michael Schärer; Anne Peutzfeldt (Medical Journals Sweden, 2022)
Objectives: To investigate the impact of adhesive application errors on dentin bond strength of resin composite.Material and Methods: 165 extracted permanent human molars were ground to mid-coronal dentin. The dentin specimens were treated with one of three adhesive systems (OptiBond FL, Clearfil SE, Scotchbond Universal) either according to manufacturer's instructions or with systematic errors in the application procedure and before application of resin composite (Filtek Z250). After storage (37 °C, 100% humidity, 24 h) shear bond strength (SBS) was measured and data analysed with either one-way ANOVA followed by Tukey tests (OptiBond FL, Scotchbond Universal, control groups) or Kruskal-Wallis followed by Wilcoxon tests (Clearfil SE). Finally, the failure mode of all specimens was assessed.Results: With OptiBond FL and Clearfil SE omitted application (p ≤ 0.0001) as well as no evaporation (p ≤ 0.001) of the solvents in the primer significantly reduced the SBS. Omitted application of the adhesive, respectively the bond, had a negative influence on the SBS of Clearfil SE (p < 0.0001), but not of OptiBond FL (p = 0.776). With Scotchbond Universal, no evaporation of the solvents (p < 0.0001) as well as no light-cure (p = 0.0004) had a significant negative influence on the SBS. Using the adhesive systems according to manufacturer's instructions, Clearfil SE achieved significantly lower SBS than OptiBond FL and Scotchbond Universal (p = 0.0027). Adhesive failure at the dentin surface was generally the most frequent failure mode observed.Conclusion: All three adhesive systems tested were sensitive to application errors. For optimal result and longest possible durability of resin restorations, clinicians should strictly adhere to the manufacturer's instructions.